Optimized Karatsuba squaring on 8‐bit AVR processors. Issue 18 (18th May 2015) - Seo, Hwajeong; Liu, Zhe; Choi, Jongseok; Kim, Howon
Abstract: Multi‐precision squaring is one of the performance‐critical operations for implementation of elliptic curve cryptography. This paper continues the line of research on high‐speed multi‐precision squaring on embedded processors. In particular, we present an optimized Karatsuba squaring method for 8‐bit AVR processors. We compute the multiplication part with the fastest Karatsuba multiplication, and then the remaining two squaring parts are conducted with the fastest sliding block doubling squaring. As a result, The proposed method sets the new speed records for multi‐precision squaring, improving the execution time by up to 8.49% compared with the best known works. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, we present an optimized Karatsuba squaring method for 8‐bit AVR processors.We compute the multiplication part with the fastest Karatsuba multiplication, and then the remaining two squaring parts are conducted with the fastest sliding block doubling squaring.